Pengaruh Wirid Surah Al-Mulk Terhadap Belajar Santri Di Madrasah Aliyah Asy-Syafi’iyyah Sidoarjo (Studi Living Qur’an) - Deki Ridho Adi Anggara; Yassirly Dita Amriya; Muh. Makhrus Ali Ridho (Universitas Darussalam Gontor, 2023)
The problem in the learning process is that it is difficult to understand and memorize lessons, this is due to reduced concentration so as to slow down the comprehension and make memory decrease, to overcome this problem there is a practice carried out in Madrasah Aliyah Ash-Syafi'iyyah Sidoarjo, namely routinely reading the Qur'an surah al-Mulk before starting the learning process. Surah al-Mulk itself is believed to have content related to learning, such as seeking knowledge, forming attitudes and behaviors, and instilling skills. To know the application of Living Qur'an. Researchers want to analyze how the practice of reading surah al-Mulk in Madrasah Aliyah Ash-Syafi'iyyah Sidoarjo and what is the impact of reading surah al-Mulk in Madrasah Aliyah Ash-Syafi'iyyah Sidoarjo. This research is a field research using descriptive methods and qualitative approaches, which aims to make descriptions, drawings or paintings systematically. By taking data from school principals, teachers, and also students. The data collection techniques used are observation, interview and documentation techniques. Based on the analysis, the researcher concluded that; The activity of recitation of surah al-Mulk is practiced together and followed by all students every day before starting the lesson with the aim of expecting blessings and intercession from surah al-Mulk itself. This activity has an impact that students feel more relaxed and calm before starting learning and make them more focused, easy to understand and memorize lessons.